BRIDGING LINGUISTIC GAPS: HOW INTERNATIONAL STUDENTS INTEGRATE L1 IN ENGLISH-LANGUAGE DIGITAL CHATS - Purnomo, Alan Joko (Samudra Publisher, 2025)
This study investigates how international students strategically integrate their first language (L1) into English-language digital chats, focusing on WhatsApp interactions. While previous research has examined code-switching in classroom settings, the role of L1 in informal digital communication remains underexplored. Employing a qualitative design with naturalistic observation and document analysis, this study analyzes 137 authentic chat exchanges from students originating from Indonesia, Yemen, Thailand, and Palestine. The findings show that L1 is not used as a sign of deficiency but as a compensatory and pragmatic strategy. Two primary patterns emerge: (1) lexical code-switching, where culturally specific expressions such as “mbak,” “insyaAllah,” and “555” help maintain fluency and emotional tone, and (2) grammatical code-switching, including tag, intra-sentential, and inter-sentential forms, which support clarity and syntactic cohesion. These results demonstrate that learners rely on the full range of language resources they possess to navigate vocabulary gaps, grammatical uncertainty, and express their cultural identity. Such practices indicate not linguistic failure, but adaptive bilingual competence. The study challenges the monolingual bias in English as a Foreign Language (EFL) pedagogy by reinterpreting L1 use as a valuable asset that enhances communication in informal settings. It concludes that acknowledging L1 in digital interaction helps educators better support multilingual learners particularly in low stress, real-world contexts. The paper recommends that EFL instruction embrace strategic L1 integration as a natural and beneficial component of second language development.